The development of smart auto-feed paper shredder / Mohd Nazrul Sidek ... [et al.] - Sidek, Mohd Nazrul; Mat Zain, Mohamad Yusof; Raja Daud, Raja Mohd Noor Hafizi; Rohafauzi, Suziyani; Zulkornain, Luqmanul Hakim (2019)
Paper is an important material where it is used for many purposes worldwide. Due to this, the amount of paper waste also increases. This paper presents an innovation derived from conventional paper shredders. The main objective is to effectively dispose used paper. Currently, users need to wait and shred the unwanted paper manually and this consumes a lot of valuable time. Putting this critical problem into concern, an innovative product with upgrades on the way of disposing unwanted paper is proposed. The process of paper shredding is upgraded, taking into consideration the analysis on how people dispose unwanted papers. This project is divided into two parts which are software and hardware developments. The main process involved in this project is cutting paper into chad, typically in strips or fine particles. The development of this shredder involved using two infrared (IR) sensors. The first sensor is used to detect the existance of paper. If paper exists, the motor will turn on, driving a roller. The roller will grab the paper and bring them to the blade for shredding process. In the meantime, there is another IR sensor in a dustbin which is used to detect the storage being either full or not. If full, the shredder will stop the shredding process until the user clears the dustbin. In a nutshell, the way of disposing unwanted paper should not be a problem as this shredder will dispose them automatically and effectively. The benefits of this shredder are the reduction of labor and time resulting in cost reduction in paper shredding operation.